Russia’s public external debt: current state, dynamics - N. A. Ivanova (Путеводитель предпринимателя)
Public debt is an important financial indicator that reflects the financial stability and ability of the state to fulfill its financial obligations. The subject of the study is the problem of public external debt, its current state, forecast for the following periods. The applied research methods are theoretical (analysis, synthesis, analogy, specification and practical comparison and observation). The author provides segments on which the repayment of external debt depends, the principles of public external borrowing. The article analyzes the current state of the public external debt. In conclusion, recommendations are given for reducing the public external debt.